Automobile air conditioning system, PTC embedded catalytic filter element and preparation method thereof

CN122998837APending Publication Date: 2026-10-30DONGFENG MOTOR GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611125318.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0031]本发明中,将PTC加热元件嵌入到金属泡沫载体的三维孔道内部,形成了嵌入式的三维网状结构,PTC加热膜与金属泡沫骨架直接紧密接触,接触热阻极小,配合金属泡沫载体自身的高导热系数,热量能够迅速通过高导热率的金属骨架传递至整个载体;加热元件分布于载体的立体空间内部,而非仅从单面加热,因此热量分布更加均匀,避免了层压式结构中常见的表面温度高、内部温度低的热梯度问题;这避免了传统层压式结构中因接触热阻导致的局部加热不均、热量传递效率低下等问题,确保了热量均匀传递到载体上的催化剂;PTC加热元件能够主动、精准地将催化区域加热至最佳反应温度(200-400℃),确保了催化剂在高效区间稳定运行,大幅提升了挥发性有机物(VOC)的净化效果和效率,由于加热效率高且热量分布均匀,达到目标温度所需的电能消耗更低,有利于新能源汽车的续航保持。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998837A_ABST
    Figure CN122998837A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of PTC embedded catalytic filter element for automobile air conditioner, including filter element shell, metal foam carrier, catalyst and PTC heating element, the metal foam carrier is installed in the filter element shell, the catalyst is loaded on the metal foam carrier, the PTC heating element is embedded inside the pore of the metal foam carrier.In addition, it is also related to the preparation method of PTC embedded catalytic filter element and the automobile air conditioning system using the PTC embedded catalytic filter element.The PTC heating element of the present application is embedded inside the three-dimensional pore of metal foam carrier, forms embedded three-dimensional network structure, cooperates with the high thermal conductivity of metal foam carrier itself, heat can be efficiently and uniformly transmitted to the whole carrier, avoid local heating uneven, heat transfer efficiency is low and other problems;PTC heating element can actively and accurately heat the catalytic region to the optimum reaction temperature, ensure that catalyst runs stably in efficient interval.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of automotive air conditioning technology, specifically relating to a PTC embedded catalytic filter for automotive air conditioning, a method for preparing the PTC embedded catalytic filter, and an automotive air conditioning system using the PTC embedded catalytic filter. Background Technology

[0002] With the continuous growth of global car ownership and the increasing public awareness of health, in-vehicle air quality has become a major concern. The relatively enclosed space of a car, coupled with the continuous release of pollutants from interior materials (such as leather and plastic) and the infiltration of exhaust fumes from incomplete combustion, can easily lead to excessive concentrations of pollutants such as formaldehyde, total volatile organic compounds (TVOC), and benzene compounds. This not only causes sensory discomfort but also poses a long-term threat to the health of drivers and passengers.

[0003] Among numerous air purification technologies, catalytic oxidation has been widely studied due to its advantages such as high purification efficiency and no secondary pollution. This technology utilizes a catalyst to deeply oxidize volatile organic compounds (VOCs) into harmless carbon dioxide and water at relatively low temperatures of 200-400℃, making it a highly efficient means of treating hydrocarbon waste gas and eliminating odors. However, traditional catalytic oxidation technology faces two challenges in practical applications: firstly, catalysts supported by granular or honeycomb ceramics generally suffer from insufficient mechanical strength, high mass transfer resistance, and easy shedding or saturation of active components; secondly, the available engine waste heat in traditional fuel vehicles is limited, and the exhaust temperature is usually below 100℃, making it difficult to directly meet the ignition temperature of the catalyst, severely restricting its purification efficiency.

[0004] To address the aforementioned bottlenecks, research has shifted its focus to developing novel catalyst supports and system integration solutions. On one hand, porous metal materials (such as metal fibers and metal foams), with their advantages of regular structure, high porosity, and low pressure drop, are considered ideal catalyst supports. On the other hand, the widespread adoption of new energy vehicles offers a new path to solving the temperature problem, as they can utilize the advantages of electricity to achieve precise temperature control through PTC heating elements. However, how to integrate high-efficiency catalysts and heating elements into a single design to achieve rapid local heating and uniform heat distribution in the catalytic region, thereby ensuring efficient and stable operation of the catalytic reaction with low energy consumption, remains a core challenge in current technological development. Summary of the Invention

[0005] This invention relates to a PTC embedded catalytic filter for automotive air conditioning, a method for preparing the PTC embedded catalytic filter, and an automotive air conditioning system using the PTC embedded catalytic filter, which can at least solve some of the defects of the prior art.

[0006] This invention relates to a PTC embedded catalytic filter element for automotive air conditioning, comprising:

[0007] Filter cartridge housing;

[0008] A metal foam carrier is installed inside the filter element housing;

[0009] A catalyst, wherein the catalyst is supported on the metal foam carrier;

[0010] The PTC heating element is embedded inside the pores of the metal foam carrier.

[0011] As one embodiment, the catalyst is obtained by loading a catalyst slurry onto the metal foam support, and then drying and calcining the loaded metal foam support. The catalyst slurry comprises the following components: 30-50 g / L polyethylene glycol, 15-25 g / L polyvinylpyrrolidone, 5-15 g / L sodium dodecylbenzenesulfonate, 5-15 g / L ethanol, and 60-100 g / L catalyst powder.

[0012] As one embodiment, the pH value of the catalytic slurry is 8.0~9.0.

[0013] As one embodiment, the drying temperature is 80~120℃ and the drying time is 2~4 hours; the calcination is carried out in an air atmosphere, the calcination temperature is 300~500℃ and the calcination time is 2~5 hours.

[0014] This invention also relates to a method for preparing a PTC embedded catalytic filter element for automotive air conditioning, comprising:

[0015] A metal foam carrier is provided, and the metal foam carrier is pretreated;

[0016] A catalyst is loaded onto the metal foam support;

[0017] A PTC heating element is embedded inside the pores of the metal foam carrier;

[0018] A metal foam carrier loaded with catalyst and embedded with PTC heating element is assembled into the filter element housing.

[0019] As one embodiment, the catalyst loaded on the metal foam support specifically includes:

[0020] A catalytic slurry is prepared and loaded onto the metal foam carrier;

[0021] The loaded metal foam carrier is then dried and calcined.

[0022] The catalyst slurry comprises the following components: 30-50 g / L polyethylene glycol, 15-25 g / L polyvinylpyrrolidone, 5-15 g / L sodium dodecylbenzenesulfonate, 5-15 g / L ethanol, and 60-100 g / L catalyst powder.

[0023] As one embodiment, the drying temperature is 80~120℃ and the drying time is 2~4 hours; the calcination is carried out in an air atmosphere, the calcination temperature is 300~500℃ and the calcination time is 2~5 hours.

[0024] As one embodiment, the pH value of the catalytic slurry is 8.0~9.0.

[0025] As one implementation method, the pretreatment of the metal foam carrier specifically includes:

[0026] The metal foam carrier was immersed in an organic solvent for ultrasonic cleaning, and then rinsed with deionized water.

[0027] The cleaned metal foam carrier is immersed in an acid solution and treated at 50-70°C for 30-60 minutes.

[0028] After rinsing the acid-soaked metal foam carrier until it is neutral, dry it at 80~120℃ for 2~4 hours.

[0029] The present invention also relates to an automotive air conditioning system, including a catalytic filter element, wherein the catalytic filter element is the above-mentioned PTC embedded catalytic filter element, or is prepared by the above-mentioned preparation method.

[0030] The present invention has at least the following beneficial effects:

[0031] In this invention, a PTC heating element is embedded within the three-dimensional channels of a metal foam carrier, forming an embedded three-dimensional mesh structure. The PTC heating film is in direct and close contact with the metal foam skeleton, resulting in minimal contact thermal resistance. Combined with the high thermal conductivity of the metal foam carrier itself, heat can be rapidly transferred to the entire carrier through the highly thermally conductive metal skeleton. The heating element is distributed throughout the three-dimensional space of the carrier, rather than heating from only one side, thus resulting in a more uniform heat distribution and avoiding the thermal gradient problem common in laminated structures, where the surface temperature is high and the internal temperature is low. This avoids the problems of uneven local heating and low heat transfer efficiency caused by contact thermal resistance in traditional laminated structures, ensuring that heat is uniformly transferred to the catalyst on the carrier. The PTC heating element can actively and precisely heat the catalytic region to the optimal reaction temperature (200-400℃), ensuring stable operation of the catalyst within the high-efficiency range, significantly improving the purification effect and efficiency of volatile organic compounds (VOCs). Due to the high heating efficiency and uniform heat distribution, the energy consumption required to reach the target temperature is lower, which is beneficial for maintaining the range of new energy vehicles. Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0033] Figure 1 A flowchart illustrating the preparation method of the PTC embedded catalytic filter element provided in this embodiment of the invention. Detailed Implementation

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] Example 1

[0036] This invention provides a PTC embedded catalytic filter element for automotive air conditioning, comprising:

[0037] Filter cartridge housing;

[0038] A metal foam carrier is installed inside the filter element housing;

[0039] A catalyst, wherein the catalyst is supported on the metal foam carrier;

[0040] The PTC heating element is embedded inside the pores of the metal foam carrier.

[0041] Preferably, the metal foam carrier includes, but is not limited to, foamed stainless steel and foamed titanium. Both foamed stainless steel and foamed titanium have good mechanical strength, corrosion resistance, and thermal conductivity, which can meet the long-term use requirements under harsh vehicle operating conditions.

[0042] Optionally, the metal foam carrier has a size of (100~300mm)×(100~300mm), a thickness of 0.5~2mm, a pore size range of 1~10mm, and a porosity of 80%-95%.

[0043] In one embodiment, the catalyst is obtained by loading a catalytic slurry onto a metal foam support, followed by drying and calcining the loaded metal foam support. Through the slurry coating combined with drying and calcination, the catalyst particles can firmly adhere to the three-dimensional framework surface of the metal foam support, forming a uniform, dense, and strongly adherent catalytically active coating. This improves the bonding strength and loading uniformity between the catalyst and the support, thereby enhancing the catalyst's stability and lifespan.

[0044] Preferably, the catalyst slurry comprises the following components: 30–50 g / L polyethylene glycol, 15–25 g / L polyvinylpyrrolidone, 5–15 g / L sodium dodecylbenzenesulfonate, 5–15 g / L ethanol, and 60–100 g / L catalyst powder. Polyethylene glycol, as a dispersant and thickener, improves the uniformity and stability of the slurry while adjusting its viscosity to suit coating operations. Polyvinylpyrrolidone, as a binder, enhances the bonding force between the catalyst particles and the metal foam skeleton after calcination, effectively preventing the active components from detaching under airflow. The carbon skeleton generated during calcination assists in anchoring the catalyst particles on the metal surface. Sodium dodecylbenzenesulfonate, as a surfactant, reduces the surface tension of the slurry, improving its wettability and spreadability on the metal surface. Ethanol, as a solvent and defoamer, regulates the evaporation rate of the slurry and improves the density of the coating layer. The catalyst powder is the active core of the catalytic oxidation reaction, responsible for the deep oxidation of VOCs into carbon dioxide and water.

[0045] Preferably, the pH value of the catalytic slurry is 8.0 to 9.0. Under the above-mentioned weakly alkaline conditions, the components can be fully dissolved and dispersed, while also promoting the negative charge on the surface of the catalyst particles, enhancing the electrostatic repulsion between particles, preventing slurry agglomeration and sedimentation, and improving coating uniformity.

[0046] Preferably, the drying process is carried out at a temperature of 80–120°C for 2–4 hours; the calcination process is carried out in an air atmosphere at a temperature of 300–500°C for 2–5 hours. Through the above drying and calcination processes, the solvent in the slurry is completely evaporated, the organic binder and dispersant are thermally decomposed and removed, and a strong sintered bond is formed between the catalyst particles and between the catalyst and the metal framework, resulting in a supported catalyst with good mechanical strength and catalytic activity.

[0047] Preferably, the PTC heating element is a flexible PTC heating film, which can be produced by cutting a whole piece of flexible PTC heating film into strips and embedding them into the pores of a metal foam carrier. The flexible PTC heating film has a positive temperature coefficient, which allows it to automatically increase resistance and reduce power output when the temperature rises, thereby achieving a self-limiting temperature function and preventing catalyst deactivation or safety hazards caused by localized overheating.

[0048] Optionally, the width of the cut PTC heating film strips is 1–5 mm, and the length matches the pore size of the metal foam carrier. Cutting the PTC heating film into strips and embedding it into the three-dimensional channels of the metal foam forms an embedded three-dimensional mesh heating structure.

[0049] Furthermore, adjacent PTC heating film strips are connected by thermally conductive adhesive. The total power of the PTC heating elements embedded in the metal foam carrier is 100~200W.

[0050] Preferably, the embedding rate of the PTC heating element in the metal foam carrier is 50% to 80%, that is, 50% to 80% of the channels of the metal foam carrier are embedded with PTC heating elements.

[0051] In this embodiment, the PTC heating element is embedded inside the three-dimensional channels of the metal foam carrier, forming an embedded three-dimensional mesh structure. The PTC heating film is in direct and close contact with the metal foam skeleton, resulting in minimal contact thermal resistance. Combined with the high thermal conductivity of the metal foam carrier itself, heat can be rapidly transferred to the entire carrier through the highly thermally conductive metal skeleton. The heating element is distributed within the three-dimensional space of the carrier, rather than heating from only one side, thus resulting in a more uniform heat distribution and avoiding the thermal gradient problem of high surface temperature and low internal temperature common in laminated structures. This avoids the problems of uneven local heating and low heat transfer efficiency caused by contact thermal resistance in traditional laminated structures, ensuring that heat is uniformly transferred to the catalyst on the carrier. The PTC heating element can actively and precisely heat the catalytic region to the optimal reaction temperature (200-400℃), ensuring stable operation of the catalyst in the high-efficiency range, significantly improving the purification effect and efficiency of volatile organic compounds (VOCs). Due to the high heating efficiency and uniform heat distribution, the energy consumption required to reach the target temperature is lower, which is beneficial to the range maintenance of new energy vehicles.

[0052] Preferably, the filter element housing is made of high-temperature resistant engineering plastic. High-temperature resistant engineering plastics (such as polyphenylene sulfide PPS, polyether ether ketone PEEK, polyimide PI, etc.) have good heat resistance, dimensional stability, and processing performance. They can maintain structural integrity under long-term high-temperature operating conditions, while also being lightweight and having good insulation properties, making them suitable for automotive applications. A rubber sealing ring can be installed inside the filter element housing to ensure a tight seal between the filter element and the air conditioning system mounting bracket, preventing unfiltered air from leaking through the bypass.

[0053] Example 2

[0054] like Figure 1 This invention provides a method for preparing a PTC embedded catalytic filter element for automotive air conditioning, comprising the following steps:

[0055] S1, Pretreatment of the metal foam carrier;

[0056] S2, a catalyst is loaded on the metal foam support;

[0057] S3, a PTC heating element is embedded inside the pores of a catalyst-loaded metal foam carrier.

[0058] S4, assemble the metal foam carrier loaded with catalyst and embedded with PTC heating element into the shell.

[0059] In one embodiment, the pretreatment of the metal foam carrier specifically includes:

[0060] S11, the metal foam carrier is immersed in an organic solvent for ultrasonic cleaning, followed by rinsing with deionized water. Preferably, the organic solvent is selected from acetone, ethanol, or a combination thereof, and the ultrasonic cleaning time is 10-20 minutes. Ultrasonic cleaning with an organic solvent can effectively remove oil, processing residues, and organic impurities from the surface and pores of the metal foam, providing a clean surface for subsequent acid treatment and catalyst loading.

[0061] S12, the cleaned metal foam carrier is immersed in an acid solution and treated at 50–70°C for 30–60 minutes. Optionally, the acid solution is selected from dilute nitric acid or dilute sulfuric acid. Acid treatment can remove the oxide layer on the surface of the metal foam, while creating a micro-rough structure on the metal surface, increasing surface energy, and improving the wettability and adhesion of subsequent catalyst slurry on the metal surface.

[0062] S13: After rinsing the acid-soaked metal foam carrier until neutral, dry it at 80-120℃ for 2-4 hours to obtain the pretreated metal foam carrier.

[0063] In one embodiment, the catalyst loaded on the metal foam support specifically includes:

[0064] A catalytic slurry is prepared and loaded onto the metal foam carrier;

[0065] The loaded metal foam carrier is then dried and calcined.

[0066] The relevant content has been described in the above-mentioned Example 1, including the composition ratio of the catalytic slurry, the specific drying process, the calcination process, etc., and will not be repeated here.

[0067] In one embodiment, embedding a PTC heating element inside the pores of a metal foam carrier specifically includes: cutting a flexible PTC heating film into PTC heating film strips, with the strip width determined according to the pore size of the metal foam (1-5 mm) and the length matching the pore size of the metal foam; embedding the cut PTC heating film strips inside the pores of a metal foam carrier loaded with a catalyst; and electrically and thermally connecting adjacent PTC heating film strips through thermally conductive adhesive.

[0068] Example 3

[0069] This invention provides an automotive air conditioning system, including a catalytic filter element. The catalytic filter element is the PTC embedded catalytic filter element provided in Embodiment 1 above, or the catalytic filter element is prepared by the preparation method provided in Embodiment 2 above.

[0070] Example 4

[0071] This embodiment provides specific application examples of several methods for preparing PTC embedded catalytic filter elements: Specific Implementation Example 1

[0073] 1) Using a 200mm×200mm porous metal foam (foamed stainless steel) with a thickness of 1mm as a carrier, immerse it in ethanol solvent and ultrasonically clean it for 10 minutes, then rinse it with deionized water. After that, immerse it in dilute nitric acid solution and treat it at 50℃ for 60 minutes. Rinse the pretreated foam repeatedly with deionized water until neutral, and then dry it in an oven at 80℃ for 4 hours.

[0074] 2) The catalyst was loaded onto a metal foam support in the form of a catalytic slurry. The slurry composition was: 40 g / L polyethylene glycol, 20 g / L polyvinylpyrrolidone, 10 g / L sodium dodecylbenzenesulfonate, 10 g / L ethanol, and 60 g / L catalyst powder (in this example, the catalyst used was a supported Mn-Ce composite oxide catalyst with a Mn / Ce molar ratio of 1:1, the support being γ-Al₂O₃, the active component loading being 15 wt%, and the catalyst powder particle size ≤ 5 μm). The pH was adjusted to 8.0. The coated support was dried at 80°C for 4 hours and then calcined at 300°C for 5 hours in air.

[0075] Specifically, prepare the catalyst slurry according to the following ratio (based on 1L of slurry):

[0076] Weigh out 40g of polyethylene glycol (PEG-4000, average molecular weight approximately 4000), 20g of polyvinylpyrrolidone (PVP-K30), 10g of sodium dodecylbenzenesulfonate, and 10g of anhydrous ethanol. Add these components sequentially to an appropriate amount of deionized water. Stir magnetically at 500 rpm for 30 minutes at room temperature until all components are completely dissolved. Then add 60g of catalyst powder and continue stirring for 60 minutes to ensure thorough dispersion. Adjust the pH of the slurry to 8.0 with a 1mol / L ammonia solution. Finally, add deionized water to a total volume of 1L and continue stirring for 30 minutes to obtain a homogeneous and stable catalyst slurry.

[0077] The loading method is as follows: The pretreated metal foam carrier is completely immersed in the above-mentioned catalytic slurry for 5 minutes, during which time it is gently shaken to ensure that the slurry fully wets all the pore surfaces of the foam. The immersed stainless steel foam is then removed and allowed to stand at room temperature for 10 minutes to drain, allowing excess slurry to flow off naturally.

[0078] 3) Select a flexible PTC heating film with a rated voltage of 12V and a rated power density of 0.5W / cm² (self-limiting temperature of 200℃). Cut the flexible PTC heating film into strips. The strip width is determined to be 1mm according to the size of the metal foam pores. The length is the same as the size of the metal foam pores. Connect adjacent PTC heating film strips with thermally conductive adhesive and lead out the power cord. The total power is 100W.

[0079] Performance evaluation:

[0080] Following the sampling and analysis methods specified in GB / T 27630-2011 "Guidelines for Air Quality Evaluation in Passenger Cars", performance evaluation was conducted in a 3m³ sealed test chamber. The prepared catalytic filter element was installed in the air conditioning system duct of the test chamber. The air conditioning system was turned on, and PTC heating was activated to stabilize the temperature of the catalytic zone at 250℃ (monitored by an infrared thermal imager). Air containing simulated VOC pollutants (pollutant concentration simulating the actual in-vehicle environment) was introduced. After catalytic purification was activated for 10 minutes, the air at the outlet was sampled and analyzed.

[0081] The test results are as follows:

[0082]

[0083] Note: ND indicates not detected (detection limit is 0.001 mg / m³).

[0084] As shown in the table above, the catalytic filter prepared in Specific Example 1 has a good purification effect on common VOC pollutants in the vehicle at a catalytic temperature of 250℃, with a purification rate of 37.5% for benzene and 23.8% for formaldehyde. Specific Implementation Example 2:

[0086] 1) Using a 200mm×200mm porous metal foam (titanium foam) with a thickness of 1mm as a carrier, it was immersed in acetone solvent and ultrasonically cleaned for 20 minutes, followed by rinsing with deionized water. Then it was immersed in dilute sulfuric acid solution and treated at 70℃ for 30 minutes. The pretreated foam was repeatedly rinsed with deionized water until neutral, and then dried in an oven at 120℃ for 2 hours.

[0087] 2) The catalyst was loaded onto a metal foam support in the form of a catalytic slurry. The slurry composition was: 40 g / L polyethylene glycol, 20 g / L polyvinylpyrrolidone, 10 g / L sodium dodecylbenzenesulfonate, 10 g / L ethanol, and 100 g / L catalyst powder (the catalyst used in this example was a supported Pt-Pd / γ-Al₂O₃ dual noble metal catalyst, with a Pt loading of 0.5 wt%, a Pd loading of 0.3 wt%, and a catalyst powder particle size ≤ 5 μm). The pH was adjusted to 9.0. The coated support was dried at 120°C for 2 hours, and then calcined at 500°C for 2 hours in air.

[0088] For the preparation and loading methods of the catalytic slurry, please refer to Specific Example 1.

[0089] 3) Select a flexible PTC heating film with a rated voltage of 24V and a rated power density of 0.6W / cm² (self-limiting temperature 220℃). Cut the flexible PTC heating film into strips. The strip width is determined to be 5mm according to the size of the metal foam pores. The length is the same as the size of the metal foam pores. Adjacent PTC heating film strips are connected with thermally conductive adhesive. Lead out the power cord. The total power is 200W.

[0090] Performance evaluation:

[0091] The performance of the catalytic filter element prepared in Specific Example 2 was evaluated using the same test methods and conditions as in Specific Example 1.

[0092] The test results are as follows:

[0093]

[0094] As shown in the table above, the catalytic filter prepared in Specific Example 2 exhibits good purification capabilities for VOC pollutants such as benzene, toluene, ethylbenzene, xylene, formaldehyde, and acetaldehyde under PTC self-limiting heating conditions. The purification rate for ethylbenzene reaches 36.0%, and the purification rate for formaldehyde reaches 30.4%. Specific Implementation Example 3:

[0096] 1) Using a 200mm×200mm porous metal foam (stainless steel) with a thickness of 1mm as a carrier, immerse it in acetone solvent and ultrasonically clean it for 15 minutes, followed by rinsing with deionized water. Then immerse it in dilute nitric acid solution and treat it at 60℃ for 45 minutes. Rinse the pretreated foam repeatedly with deionized water until neutral, and then dry it in an oven at 100℃ for 3 hours.

[0097] 2) The catalyst was loaded onto a metal foam support in the form of a catalytic slurry. The slurry composition was: 40 g / L polyethylene glycol, 20 g / L polyvinylpyrrolidone, 10 g / L sodium dodecylbenzenesulfonate, 10 g / L ethanol, and 80 g / L catalyst powder (in this example, the catalyst used was a supported Mn-Ce-La composite oxide catalyst with a Mn / Ce / La molar ratio of 5:4:1, a γ-Al₂O₃ support, an active component loading of 20 wt%, and a catalyst powder particle size ≤3 μm). The pH was adjusted to 8.5. The coated support was dried at 100°C for 3 hours and then calcined at 400°C for 3 hours in air.

[0098] For the preparation and loading methods of the catalytic slurry, please refer to Specific Example 1.

[0099] 3) Select a flexible PTC heating film with a rated voltage of 12V and a rated power density of 0.55W / cm² (self-limiting temperature 210℃). Cut the flexible PTC heating film into strips. The strip width is determined to be 3mm according to the size of the metal foam pores. The length is the same as the size of the metal foam pores. Connect adjacent PTC heating film strips with thermally conductive adhesive and lead out the power cord. The total power is 150W.

[0100] Performance evaluation:

[0101] The performance of the catalytic filter element prepared in Specific Example 3 was evaluated using the same test methods and conditions as in Specific Example 1.

[0102] The test results are as follows:

[0103]

[0104] As shown in the table above, the catalytic filter element prepared in Specific Example 3 exhibits the best overall purification performance, showing significant removal effects on all eight tested VOC pollutants. Specifically, the purification rate for benzene reached 53.8%, for ethylbenzene 46.2%, for toluene 36.1%, for formaldehyde 34.6%, and for acetaldehyde 32.8%.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A PTC embedded catalytic filter element for automotive air conditioning, characterized in that, include: Filter cartridge housing; A metal foam carrier is installed inside the filter element housing; A catalyst, wherein the catalyst is supported on the metal foam carrier; The PTC heating element is embedded inside the pores of the metal foam carrier.

2. The PTC embedded catalytic filter element according to claim 1, characterized in that, The catalyst is obtained by loading a catalyst slurry onto a metal foam support, followed by drying and calcining the loaded metal foam support. The catalyst slurry comprises the following components: 30-50 g / L polyethylene glycol, 15-25 g / L polyvinylpyrrolidone, 5-15 g / L sodium dodecylbenzenesulfonate, 5-15 g / L ethanol, and 60-100 g / L catalyst powder.

3. The PTC embedded catalytic filter element according to claim 2, characterized in that, The pH value of the catalytic slurry is 8.0~9.

0.

4. The PTC embedded catalytic filter element according to claim 2, characterized in that, The drying process is carried out at a temperature of 80~120℃ for 2~4 hours; the calcination process is carried out in an air atmosphere at a temperature of 300~500℃ for 2~5 hours.

5. A method for preparing a PTC embedded catalytic filter element for automotive air conditioning, characterized in that, include: A metal foam carrier is provided, and the metal foam carrier is pretreated; A catalyst is loaded onto the metal foam support; A PTC heating element is embedded inside the pores of the metal foam carrier; A metal foam carrier loaded with catalyst and embedded with PTC heating element is assembled into the filter element housing.

6. The preparation method according to claim 5, characterized in that, The catalyst supported on the metal foam carrier specifically includes: A catalytic slurry is prepared and loaded onto the metal foam carrier; The loaded metal foam carrier is then dried and calcined. The catalyst slurry comprises the following components: 30-50 g / L polyethylene glycol, 15-25 g / L polyvinylpyrrolidone, 5-15 g / L sodium dodecylbenzenesulfonate, 5-15 g / L ethanol, and 60-100 g / L catalyst powder.

7. The preparation method according to claim 6, characterized in that, The drying process is carried out at a temperature of 80~120℃ for 2~4 hours; the calcination process is carried out in an air atmosphere at a temperature of 300~500℃ for 2~5 hours.

8. The preparation method according to claim 6, characterized in that, The pH value of the catalytic slurry is 8.0~9.

0.

9. The preparation method according to claim 5, characterized in that, The pretreatment of the metal foam carrier specifically includes: The metal foam carrier was immersed in an organic solvent for ultrasonic cleaning, and then rinsed with deionized water. The cleaned metal foam carrier is immersed in an acid solution and treated at 50-70°C for 30-60 minutes. After rinsing the acid-soaked metal foam carrier until it is neutral, dry it at 80~120℃ for 2~4 hours.

10. An automotive air conditioning system, comprising a catalytic converter filter, characterized in that, The catalytic filter element is the PTC embedded catalytic filter element according to any one of claims 1 to 4, or is prepared by the preparation method according to any one of claims 5 to 9.